How Artificial Intelligence Influences ESG Investment Decisions on Digital Platforms: The Mediating Role of Investor Trust - K, Sivabharathi; R, Sridharan (International Journal of Aquatic Research and Environmental Studies, 2026)
Artificial Intelligence (AI) is transforming digital investment platforms by providing personalised investment recommendations, predictive analytics, and real-time decision support. At the same time, Environmental, Social, and Governance (ESG) investing has gained increasing importance as investors seek sustainable investment opportunities. However, limited empirical research has examined how AI influences ESG investment decisions through investor trust, particularly among retail investors in emerging economies. This study investigates the effect of Artificial Intelligence Capabilities on ESG Investment Decisions, with Investor Trust serving as a mediating variable. A quantitative, cross-sectional research design was adopted, and data were collected from 324 retail investors using AI-enabled digital investment platforms in Chennai, India. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4. The findings indicate that AI Capabilities significantly enhance Investor Trust and positively influence ESG Investment Decisions. Furthermore, Investor Trust partially mediates the relationship between AI Capabilities and ESG Investment Decisions. The study contributes to the literature on AI, FinTech, sustainable finance, and behavioural finance by demonstrating the role of investor trust in promoting ESG investing. The findings also provide practical implications for digital investment platform providers, financial institutions, and policymakers in developing transparent, reliable, and trustworthy AI systems that encourage sustainable investment behaviour.